A novel three-stage modification method for enhancing the performance of rubber concrete: Shear-embedding of nanoparticles, heat treatment, and gel-based surface reconstruction of waste rubber particles - Yuan Jing; Mingjin Yan; Jidong Liu; Kun Li; Guangyi Lin (Journal of Cleaner Production, 2026)

Application of antimony stable isotopes in revealing the source and migration of Sb in rivers - Xinyu Li; Guangyi Sun; Yunjie Wu; Yu Lin; Chenmeng Yang; Xinbin Feng (Water Research, 2026)

Enhancing anaerobic digestion of dairy wastewater with Fe3O4@BVRs: Performance and mechanisms - Zisheng Zhao; Haoyang Yu; Yixin Li; Huiyang Li; Sihao Lin; Yiming Ji; Yusen Li; Xiaowei Wang; Guangyi Zhang (Journal of Water Process Engineering, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

A membrane-mediated algal–bacterial coupling strategy for energy – efficient and low-carbon PHA production - Long Huang; Lin Liu; Guangyi Zhang; Guoqiang Li; Yingke Fang; Yuan Li; Huiying Yang; Hongbin Xu (Bioresource Technology, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Maternal prenatal mercury exposure from rice and its association with newborn neurobehavioral development - Chunfang Gan; Xinbin Feng; Kun-Lin Yang; Guangyi Sun; Weijun Luo; Qiang Yang; Wenjin Zhang; Yan Shi; Li Wang; Min Xiong; Mahmoud A. Abdelhafiz (Environmental Pollution, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

The progress of research on thermally active walls - Chongzhi Guo; Wanxiang Yao; Guangyi Zhang; Zhaozhao Fang; Yan Wang; Dahu Lin; Weijun Gao; Weiyou Guo (Building and Environment, 2026)

Synergistically promoting humification and polluting gas reduction in cherry tomato straw composting via carbon bioavailability management - Jiacong Lin; Guangyi Li; Dingmei Wang; Yuqi Pang; Zhuoya Han; Xingwei Meng; Liwen Mai; Shiliang Peng; Qinfen Li (Environmental Pollution, 2025)

KHDC3 affects the lineage differentiation of early embryo by regulating the differential distribution of YAP signal - Qian Xu; Yuling Lin; Lina Yu; Yang Zhang; Na Kong; Guijun Yan; Haixiang Sun; Guangyi Cao (Theriogenology, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

Exposure to polyethylene terephthalate micro(nano)plastics exacerbates inflammation and fibrosis after myocardial infarction by reprogramming the gut and lung microbiota and metabolome - Xin Gu; Zhixuan Zhang; Lin Zhao; Lijie Lu; Xin Lu; Yafei Li; Tianya Gu; Xin Huang; Guangyi Huang; Yan Liang; Haoyu Meng; Baihong Li; et al. (Journal of Hazardous Materials, 2025)

A review on the recent developments in vision-based apple-harvesting robots for recognizing fruit and picking pose - Yanqiang Zhang; Na Li; Lijie Zhang; Jianfeng Lin; Xiao Gao; Guangyi Chen (Computers and Electronics in Agriculture, 2025)

The first genetically confirmed live sighting of the Deraniyagala's beaked whale ( Mesoplodon hotaula ), with insights into the diversity, phylogeny, and past demographic history - Wenzhi Lin; Hui Kang; Inge Seim; Binshuai Liu; Shenglan Chen; Mingming Liu; Lijun Dong; Mingli Lin; Yuhang Song; Mingyue Ouyang; Xiaoyu Huang; Yingxue Gao; et al. (Marine Mammal Science, 2025)
Beaked whales have recently been reported in the South China Sea but with taxonomic uncertainty due to their ambiguous morphological features. Here, we sequenced three genetic markers, the control region (CR) and cytochrome b ( cytb ) of the mitochondrial genome and the first intron of the nuclear muscle actin gene ACTA2 , of two biopsy samples collected in 2021, and revealed unambiguous clustering with sequences previously attributed to Deraniyagala's beaked whale ( Mesoplodon hotaula ). Phylogenetic analysis of complete mitogenomes strongly supported the close relationship between the Deraniyagala's beaked whale and the ginkgo‐toothed beaked whale ( M. ginkgodens ). Whole‐genome sequencing suggested a high degree of heterozygosity in the Deraniyagala's beaked whale. Ancient inbreeding may have had a greater impact than the recent inbreeding on Deraniyagala's beaked whales, but more samples are needed to draw a firm conclusion. The approximate effective population size of Deraniyagala's beaked whale was found lowest among seven examined ziphiids, which has been experiencing a steady decline since ~300,000 ya. Therefore, we suggest that the conservation status of Deraniyagala's beaked whales should be assessed when essential information is available. The results of our study provide genetic evidence of the live sighting of Deraniyagala's beaked whale in the South China Sea and are fundamental to understanding the morphological, behavioral, and ecological perspectives of this cetacean species.

Integrated membrane process of tubular ultrafiltration-nanofiltration-electrodialysis-reverse osmosis for treating fracturing flowback fluid - Bing Xu; Qian Zhang; Huanhuan Wu; Qianqian Tian; Wenming Chai; Ming Zhang; Guangyi Shao; Shuwen Tian; Yakai Lin; Hong Yao (Journal of Cleaner Production, 2024)

The composition and differences of antimony isotopic in sediments affected by the world's largest antimony deposit zone - Huiji Liu; Guangyi Sun; Mengchang He; Xinbin Feng; Chunye Lin; Wei Ouyang; Xitao Liu (Water Research, 2024)

Accelerating the humification of mushroom waste by regulating nitrogen sources composition: Deciphering mechanism from bioavailability and molecular perspective - Jiacong Lin; Yilin Mao; Liwen Mai; Guangyi Li; He Liu; Shiliang Peng; Dingmei Wang; Qinfen Li; Zhen Yu; Jing Yuan; Guoxue Li (Chemosphere, 2024)

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Effects of heavy metal exposure on hypertension: A machine learning modeling approach - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Chemosphere, 2023)

Association between co-exposure to phenols, phthalates, and polycyclic aromatic hydrocarbons with the risk of frailty - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Environmental Science and Pollution Research, 2023)

Distribution, Source Identification, and Output flux of Barium in Surface Waters in the Sanjiangyuan Region and Qilian Mountain Region of Tibetan Plateau - Zuxiu Yao; Guangyi Sun; Li Lin; Wei Zhang; Junfang Zhang; Lingjian Gao; Lihai Shang (Bulletin of Environmental Contamination and Toxicology, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Chromosome-Level Genome Assembly of the Rough-Toothed Dolphin (Steno bredanensis) - Haiyu Gao; Hui Kang; Yaolei Zhang; Jiahao Wang; Wenzhi Lin; Peijun Zhang; Mingli Lin; Mingming Liu; Guangyi Fan; Songhai Li (Journal of Marine Science and Engineering, 2023)
The rough-toothed dolphin (Steno bredanensis), the single extant species of the genus Steno, inhabits tropical and subtropical oceans. It is an attractive species for studying aquatic adaptation and evolution. The latest advances in high-throughput sequencing are transforming the study of marine mammals and contributing to understanding various phenomena at the species and population level by determining high-quality genomes. Here, to comprehensively understand the genetic features and explore the molecular basis of aquatic adaption, the chromosome-level genome assembly and comparative genomics analyses of S. bredanensis were performed. The 2.30 Gb final genome assembly of S. bredanensis (scaffold N50 length of 105.53 Mb) was obtained using single-tube long fragment read (stLFR) and Hi-C technologies. The genome assembly clearly revealed the preservation of large chromosomal fragments between S. bredanensis and the melon-headed whale (Peponocephala electra). The S. bredanensis genome contained 19,451 predicted protein-coding genes, of which about 92.33% have functional annotations. The genome assembly and gene sets showed high completeness, with a BUSCO score of 90.6% and 97.3%, respectively. We also identified several positively selected genes specific to S. bredanensis, which may be related to fat cell differentiation, tooth morphogenesis, and immunoregulatory activity. Finally, the demographic dynamics of S. bredanensis were estimated by the pairwise sequentially Markovian coalescent (PSMC) model and found that the population was affected by the climate at the time. We demonstrated that improved continuity and accuracy of the assembled sequence warranted the adoption of this chromosome-level genome as the reference genome and advanced the understanding of genetic features of the rough-toothed dolphin, which will be essential for future evolutionary studies and the protection of this species.

Experimental and Numerical Investigations on the Macro-Meso Shear Mechanical Behaviors of Artificial Rock Discontinuities with Multiscale Asperities - Xinrong Liu; Bin Xu; Guangyi Lin; Junhui Huang; Xiaohan Zhou; Yingkun Xie; Jiwen Wang; Fei Xiong (Rock Mechanics and Rock Engineering, 2021)

Probing the distribution and contamination levels of 10 trace metal/metalloids in soils near a Pb/Zn smelter in Middle China - Zhonggen Li; Xinbin Feng; Xiangyang Bi; Guanghui Li; Yan Lin; Guangyi Sun (Environmental Science and Pollution Research, 2014)